2017
DOI: 10.1371/journal.pone.0186523
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of activity monitors used in Asian and Western-country studies for assessing free-living sedentary behaviour

Abstract: This study aims to compare the outputs of the waist-worn Active style Pro HJA-350IT (ASP; used in studies with Asian populations), the waist-worn ActiGragh™GT3X+ using the normal filter (GT3X+) and the thigh-worn activPAL3 (AP) in assessing adults’ sedentary behaviour (total sedentary time, number of breaks) under free-living conditions. Fifty healthy workers wore the three monitors simultaneously during their waking hours on two days, including a work day and a non-work day. Valid data were at least 10 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 36 publications
0
67
0
Order By: Relevance
“…The participants’ PA was assessed using an accelerometer (Active style Pro HJA-350IT, Omron Healthcare, Kyoto, Japan). The detailed algorithm and validity of the accelerometer device have been described elsewhere [ 17 19 ]. Briefly, the device (74 × 34 × 46 mm; 60 g) measures anteroposterior (x-axis), mediolateral (y-axis), and vertical (z-axis) acceleration signals.…”
Section: Methodsmentioning
confidence: 99%
“…The participants’ PA was assessed using an accelerometer (Active style Pro HJA-350IT, Omron Healthcare, Kyoto, Japan). The detailed algorithm and validity of the accelerometer device have been described elsewhere [ 17 19 ]. Briefly, the device (74 × 34 × 46 mm; 60 g) measures anteroposterior (x-axis), mediolateral (y-axis), and vertical (z-axis) acceleration signals.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain generalizable findings, a study with high comparability (i.e., cluster randomized controlled trial) and a larger sample size should be conducted. Second, the accelerometer used in this study has been reported to underestimate the duration of SB and overestimate breaks from prolonged SB compared to thigh-worn activPAL3 [21]; thus, direct comparisons with previous studies using different devices should be performed cautiously. Third, video analysis was conducted without identifying an individual participant owing to compliance with the ethical agreement, and hence the result of the accelerometer and the video analysis could not be combined.…”
Section: Discussionmentioning
confidence: 83%
“…A triaxial-accelerometer with an epoch length of 60 s (Active style Pro HJA-750C; Omron Healthcare Co. Ltd., Kyoto, Japan) was used for the measurement of the activities in this study. The validity of the device for the measurement of PA and SB has been examined and reported in prior studies [18][19][20][21].…”
Section: Physical Activity and Sedentary Behaviormentioning
confidence: 99%
“…The duration and intensity of physical activity in free-living conditions were evaluated using a triaxial accelerometer (Active Style Pro HJA-350IT; Omron Healthcare; Muko, Kyoto, Japan) [40,41]. The accelerometer was attached to the waist of each subject during waking hours for 7 days, including both weekdays and weekends.…”
Section: Evaluation Of Physical Activitymentioning
confidence: 99%